Narrative inquiries into curriculum-making in teacher education - Kitchen, Julian; Parker, Darlene Ciuffetelli; Pushor, Debbie (Bingley, U.K. : Emerald, 2011)
The authors explore how individuals identity and personal practical knowledge are being formed, shifted or interrupted through moments in teacher education which the authors have carefully and thoughtfully constructed. The particularity of the stories, expressed in this collection, provide us with multiple perspectives and multiple entry points into making deeper sense of the complexity of curriculum-making in teacher education. As the stories of experience resonate with our own or as they stand apart from them, they provoke us to re-imagine teacher education, and to retell and relive our own stories of teacher education with new possibility. Narrative inquiry offers teacher educators a way to move the telling of stories of curriculum- making in teacher education forward, to delve more deeply into stories in order to make sense of experience and to attend more closely to a curriculum of life that is educative for the self and others in teacher education.
Narrative inquiry, curriculum making, and teacher education / Darlene Ciuffetelli Parker, Debbie Pushor, Julian Kitchen -- Narrative inquiry in teaching and teacher education / Cheryl J. Craig -- Narrating the tensions of teacher educator researcher in moving story to research / Stefinee Pinnegar, Mary Lynn Hamilton -- Teaching for the love of it : an education professor's narrative at the crossroads of language, culture and identity / Grace Feuerverger -- Storying curriculum making in a collaborative research and teaching landscape / Ruth Mansur, Smadar Tuval, Judith Barak, Bobbie Turniansky, Ariela Gidron, Talia Weinberger -- Imagining and re-imagining our students and ourselves : using metaphor to story the experiences of teacher candidates and teacher educators / Julian Kitchen -- Related literacy narratives : letters as a narrative inquiry method in teacher education / Darlene Ciuffetelli Parker -- Social studies teacher educators as curriculum makers : engaging teacher candidates in democratic practices / Lynette B. Erickson, Amy B. Miner -- Tip-toeing past the fear : becoming a music educator by attending to personal music experiences / Shelley M. Griffin -- Storied ways of approaching diversity : reconceptualizing a blended learning environment in a multicultural teacher education course / Ramona Maile Cutri -- Attending to milieu : living a curriculum of parents / Debbie Pushor -- Making curriculum of lives : living a story of critical literacy / Dixie K. Keyes -- In curriculum of life on narrative inquiry / Shijing Xu -- Turning points : reflections on the autumn leaves / Debbie Pushor, Julian Kitchen, Darlene Ciuffetelli Parker.
Print version record
Keywords: Education -- Research; Education -- Curricula; Education -- General; Curriculum planning & development; Philosophy & theory of education; Teachers -- Training of; Curriculum planning